Border and territorial disputes of the world - Calvert, Peter; Alcock, Antony; Beck, Peter; Collins, Alan; Day, Stephen; Faal, Mohammed; Freedman, Jane; Glenn, John; Hryb, Olexander; Joffee, Lawrence; Katajala, Kimmo; Littlewood, Jez; et al. (John Harper Publishing Distributed exclusively in the U.S. and Canada by Gale Group, 2004)
Disputes over territory remain a potent source of conflict in many parts of the world. Border and Territorial Disputes of the World is packed with information on 100 such disputes. Each entry provides a wealth of historical and current data - origin, developments, current status - and is illustrated by a map